Public Microeconomics - Singer, Neil M. (Boston : Little Brown, 1972)
The emphasis of the book is on economic analysis, especially on the integration of microeconomic theory with governmental resource allocation.
Includes bibliographies.
osc 12/06/17
Loans
Keywords: Taxation; Finance, Public; United States